Features of Structural, Energy and Kinetic Characteristics of Hf1-xErxNiSn Solid Solution - Romaka, L.P.; Rogl, P.-F.; Нoryn A.M.; Romaka, V.V.; Krayovskyy, V.Ya.; Stadnyk, Yu.V. (Physics and Chemistry of Solid State, 2016)
1-xErxNiSn solid solution in the range: T = 80 – 400 K, x = 0 - 0.10. It was confirmed partly disorder crystal structure of HfNiSn compound as a result of occupation in the 4a crystallographic site of Hf (5d26s2) atoms by Ni (3d84s2) ones up to 1 % that generates in the crystal structural defects of donor nature. It was shown that introduction of Er atoms ordered crystal structure (“healing” of structural defects). It was established mechanisms of simultaneous generation of structural defects as acceptors by substitution of Hf (5d26s2) by Er (4f125d06s2) atoms, and the donor nature defects as a result of the appearance of vacancies in the Sn (4b) atoms sites, which determines the mechanisms of conductivity for Hf1-xErxNiSn.